Service-oriented computing : 10th International Conference, ICSOC 2012, Shanghai, China, November 12-15, 2012. Proceedings - Liu, Chengfei (Lecture Notes in Computer Science, 2012)
This book constitutes the conference proceedings of the 10th International Conference on Service-Oriented Computing, ICSOC 2012, held in Shanghai, China in November 2012. The 32 full papers and 21 short papers presented were carefully reviewed and selected from 185 submissions. The papers are organized in topical sections on service engineering, service managment, cloud, service QoS, service security, privacy and personalization, service applications in business and society, service composition and choreography, service scaling and cloud, process management, service description and discovery, service security, privacy and personalization, applications, as well as cloud computing.